PERTANGGUNG JAWABAN NOTARIS AKIBAT ADANYA PEMALSUAN IDENTITAS DIRI DEBITOR DALAM AKTA PERJANJIAN KREDIT PADA BANK - NURUL AINA (PREMISE LAW JURNAL, 2016)
The importance of writing authentic credit contract as strong and legal evidence is legal guarantee for the parties involved in the contract. In drawing up   a deed, a Notary has to adjust the evidence of the person(s) appearing to the other evidence. The research used legal normative method by analyzing legal provisions and conducting interviews with informants as the source persons. The position of a notarial deed as the law for those who make it is that a Notary was liable for any evidence before him in drawing up the deeds which were gathered in the minute of the deed. When the fraud is made by the Notary himself so that someone is harmed and it violates public interest, he is liable either for civil law or for criminal law. Administrative sanction will be imposed on a Notary who is careless in receiving and examining the evidence from debtors. The sanctions are in the forms of oral notice, written notice, honorable discharge, and dishonorable discharge. Legal protection for a Notary is regulated normatively in the prevailing laws and regulation. In drawing up a deed, a Notary should pay attention to the UUJN. He does not need to be in a hurry in drawing up a deed and giving facility to the persons appearing with the reasons of providing services and trust. He and his staf as witnesses should remind to one another if he forgets to attach the identities of the persons appearing in the minutes of the deed. Keywords: Creditor, Debtor, Authentic Deed